Teachers’ Conceptions of Electromagnetic Radiation in Mobile and Wireless Technologies: The Role of Teaching Specialization and Gender - Leonidas Gavrilas; Marianna–Sotiria Papanikolaou; Konstantinos Kotsis (International Journal of Education and Teaching Zone, 2026)
Electromagnetic radiation is a fundamental scientific concept encountered daily through mobile phones, wireless networks, and other technologies. However, it is often mistakenly associated with radioactivity and health risks, leading to widespread misconceptions. This study investigated Greek teachers’ conceptions of electromagnetic radiation in mobile and wireless technologies, examining differences by teaching specialization and gender. A quantitative survey of 455 teachers from four specialization groups used ten dichotomously scored items to assess understanding of electromagnetic radiation, radioactivity, emissions from everyday technologies, and the specific absorption rate (SAR). The total score showed acceptable internal consistency for exploratory use (Cronbach’s α = .713). The mean correctness score was 40.99% (SD = 24.24), indicating substantial variability across items. In the bivariate analysis, men scored higher than women, t(453) = 5.72, p < .001. However, in the unbalanced two-way ANOVA model, the gender effect was not statistically detectable when teaching specialization and the gender-by-specialization structure of the sample were included, F(1, 447) = 0.14, p = .708, whereas specialization remained significant, F(3, 447) = 18.57, p < .001. Computer Science and Physics teachers outperformed those in Primary and Preschool Education. The findings underscore the need for teacher education to strengthen understanding of the distinctions between electromagnetic radiation and radioactivity, emissions from mobile and wireless technologies, and the specific absorption rate (SAR).